Long Term Bisphosphonate Use in Osteoporotic Patients; A Step Forward, Two Steps Back - Pooneh Salari; Mohammad Abdollahi (Journal of Pharmacy & Pharmaceutical Sciences, 2012)
Purpose. Bisphosphonates are the main class of drugs widely used in prevention and treatment of osteoporosis. Along with the beneficial effects, recent studies point to the harms of long-term treatment with bisphosphonates. Methods. The most relevant articles reporting serious adverse effects of bisphosphonates were selected and reviewed with the aim of assessing the risk-benefit of bisphosphonates. We searched PubMed, Web of Science, and Scopus using keywords bisphosphonates, risk of fracture, atrial fibrillation, osteonecrosis jaw, esophageal cancer, and adverse effects with no time limitation. We limited our s research to English articles. Results. Our review shows that bisphosphonates reduce vertebral fractures in short term use while in long-term can cause osteonecrosis jaw, esophageal cancer, atrial fibrillation, and increase the risk of atypical fractures and probably adynamic bone disease. There is no consensus on the time limitation of bisphosphonate usage or its long term adverse effects. Thus, more studies on long-term side effects of bisphosphonates are highly recommended. In addition, new approaches for prevention and treatment of osteoporosis seem necessary. Conclusion. Prescribers should act cautionary and consider full assessment of risk-benefit and the duration of treatment.